Keys to pragmatic tagging in the CHILDHUM corpus - Ortega-Gilabert, Jose Antonio; Timofeeva Timofeev, Larissa (Círculo de Lingüística Aplicada a la Comunicación, 2023)
In the context of research by the GRIALE group, one of the most recent lines of study has been the analysis of children’s verbal humour. Various projects here have focused on three age groups: 8, 10 and 12 years. The present study is based on the analysis of humorous written narratives that comprise the CHILDHUM corpus, currently under construction. The pragmatic tagging of samples drawn from CHILDHUM, over 1,000 in total for the three age groups, includes the usual sociolinguistic variables (age, sex, type of centre) but also the application of the system of humour markers and indicators (Ruiz Gurillo, 2012; Timofeeva Timofeev and Ruiz Gurillo, 2021) that act as linguistic devices in the creation of humour. An analysis of these markers and indicators will allow us to see the correlation between their use and the level of metalinguistic development of the participants. In addition, the pragmatic tagging of our corpus allows us to observe various psychosocial aspects, such as those relating to humour styles (Martin et al., 2003) and self-esteem (Pope et al., 1988; Hosogi et al., 2012), which in turn can yield linguistic data on the maturation processes of various human competencies which are in some way involved in the complex phenomenon of verbal humour.